2004
DOI: 10.1002/imhj.20025
|View full text |Cite
|
Sign up to set email alerts
|

Colic and fussing in infancy, and sensory processing at 3 to 8 years of age

Abstract: The purpose of this follow-up study was to examine whether a group of 28 clinic-referred infants with colic, excessive crying, or both at 4 to 12 weeks demonstrated sensory processing, coping, and behavioral/attention regulation difficulties at 3 to 8 years of age. Seventy-five percent of the sample demonstrated atypical behavioral responses to sensory experiences. Hours of fussing during infancy significantly correlated with inattention, emotional reactivity, touch processing, environmental coping, and extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 55 publications
5
53
0
3
Order By: Relevance
“…In line with other research our findings indicate an association between early regulatory disorders and subsequent children's psychic problems [8,15,16,19,20]. Our results show a highly statistically significant association between crying, whining and sleeping disorders at five months, and one and a half years later, for both externalized and internalized problems, controlling for the net income per household, mother's educational level, prematurity and the child`s gender, maternal distress and depressive symptoms, dysfunctional mother-child interaction and the mother's perception of her child being "difficult".…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with other research our findings indicate an association between early regulatory disorders and subsequent children's psychic problems [8,15,16,19,20]. Our results show a highly statistically significant association between crying, whining and sleeping disorders at five months, and one and a half years later, for both externalized and internalized problems, controlling for the net income per household, mother's educational level, prematurity and the child`s gender, maternal distress and depressive symptoms, dysfunctional mother-child interaction and the mother's perception of her child being "difficult".…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Desantis et al [16] found an association between duration of whining and unease in the first weeks of life, emotional reactivity and externalizing disorders from the ages of 3 to 8.…”
Section: Influence Of Regulatory Problems On Later Behavioural Problemsmentioning
confidence: 82%
“…Generally, the direct causes were incompletely understood, but it has been assumed that it is imputed to different contributors such as central nervous system pathway disturbance, inconvenient infant-family relationship, parental anxiety, and different gastrointestinal pathologies like cow's milk allergy, gastroesophegeal reflux or motility disorders. [12][13][14][15][16] Moreover, altered micro-biota theory is also suggested to affect gut motility and gas production, leading to the colicky episodes. 17 There was old concept linked to breastfeeding influential effect against infantile colic, but recently one study rejects this concept and proved that breastfeeding did not have a protective effect on the development of colic.…”
Section: Causes Of Infantile Colicmentioning
confidence: 99%
“…24 Las dificultades en la lactancia materna -tales como problemas en el acople y posicionamiento entre madre e hijo, sobrecarga funcional de lactosa, disfunción motora oral, anquiloglosia, y problemas en el procesamiento sensorialpodrían colocar a los bebés susceptibles en riesgo de afianzar conductas de aversión hacia los alimentos además del llanto y la irritabilidad. 25,26 Muchos clínicos pediatras, enfermeras pediátricas y neonatales, puericultoras y gastroenterólogos infantiles en todo el mundo, que incluyen a aquellos con actitudes positivas hacia la lactancia materna, no han advertido su falta de conocimientos en relación con la identificación y el manejo de los problemas en la alimentación.…”
Section: Problemas Con La Alimentación Y Durante Ellaunclassified